Factors influencing utilisation of learning management system among university faculty members in Saudi Arabia - Asiri, Mohammed J. Sherbib (2012)
The Jusur Learning Management System (Jusur LMS) was first introduced into the Saudi public universities in 2008. However, little is known about its utilisation and influencing factors among faculty members as not many comprehensive studies have been done related to it. A review of related literature demonstrates that factors, namely competency, attitude, barriers, pedagogical beliefs toward e-learning,and demographic variables influence technology uptake. Thus, the main objectives of the study were to identify the factors influencing the utilisation of the Jusur Learning Management System of faculty members in Saudi-Arabian universities. This study is quantitative in nature and a descriptive correlational research design was employed to gather relevant data. The population of the study comprised of faculty members from 11 public universities in Saudi Arabia (N= 18328). Based on Israel’s formula,the minimum sample size for this study was 392 faculty members. They were selected based on the cluster random sampling technique. The research instrument was in the form of an online questionnaire (http://www.smart-survey.co.uk/v.asp?i=35187abvln). A total of 710 faculty members were emailed this link, and out of this number, a total of 454 responses were valid and analyzed. The research instrument was adapted from previous studies and validated by a panel of experts from the field of Instructional Technology. The reliability of the instrument ranged from 0.71 to 0.97. The research instrument was divided into six sections, namely,demographic variables (7 items), utilisation of Jusur LMS (18 items), competency in using Jusur LMS (20 items), attitude towards Jusur LMS (20 items), barriers in using Jusur LMS (22 items), and pedagogical beliefs towards e-learning (19 items). The results of this study indicated that the faculty members’ competency, attitude, barriers, and pedagogical beliefs were related more to utilisation of Jusur LMS than the demographic variables. The utilisation level of the Jusur LMS among the faculty members in the Saudi universities was considered as at moderate level. Also found, the faculty members had positive attitude towards Jusur LMS (M= 3.68, SD= .92) and positive pedagogical belief towards e-learning (M= 3.21, SD= .86). The competency and the barrier levels in using Jusur LMS among the faculty members in Saudi universities were considered at a moderate level. Generally, the male faculty members were found to use more likely the Jusur LMS than their female counterpart. In contrast, specialization, nationality, and position did not significantly differ in the utilisation of the Jusur LMS. Also found, positive correlations existed between the utilisation of the Jusur LMS and five independent variables, which included faculty members’ competency in the use of the Jusur LMS, their attitude towards using Jusur LMS and pedagogical beliefs towards e-learning, as well as e-learning workshops and computer experience. A negative correlation existed between the utilisation of the Jusur LMS and the barriers faced by faculty members in using Jusur LMS. The multiple regression analysis showed that competency in the use of the Jusur LMS, attitude towards Jusur LMS, barriers in using Jusur LMS, and the pedagogical beliefs toward e-learning were significant predictors of the utilisation of the Jusur LMS.